THE PROBLEM OF MEDICINES INTERCHANGEABILITY. FOCUS ON PERINDOPRIL - A. I. Malyhina; M. V. Zhuravleva; A. K. Starodubtsev; M. L. Maksimov; O. A. Rogacheva (Столичная издательская компания, 2015)
Aim. To evaluate the therapeutic equivalence between generic perindopril (Parnavel, LLC Ozone, Russia) and the original perindopril (Prestarium A, Laboratories Servier, France). Material and methods. Patients with arterial hypertension, grade 1-2 (n=40, aged 35-75 years) were included into the open randomized cross-over trial. The previous anti- hypertensive therapy was discontinued before study for 14 days in all patients. Each of the patients was randomized for alternate 8-week treatment with the original (Prestarium A) and generic (Parnavel) perindopril. Treatment efficacy was assessed by the achievement of target blood pressure (BP) <140/90 mm Hg. The drug dose was increased in the efficacy lack and inapamide was added if necessary. Therapy was discontinued for 14 days after 8 weeks of treatment with the first randomization drug, and the same therapy course with the other study drug was carried out. Side effects were also recorded.Results. A significant reduction in systolic (SBP) and diastolic BP (DBP) was found in patients of Parnavel group by 28 mm Hg (19%) and 17 mm Hg (19%), respectively. In the patients of Prestarium A group SBP and DBP reduction was 27 mm Hg (18.5%) and 16 mm Hg (18.7%), respectively. After 2 months of therapy the target BP level (<140/90 mm Hg) was achieved in 95% and 90% of patients in Parnavel and Prestarium A groups, respectively. Drug tolerability was comparable.Conclusion. Efficacy and tolerability data demonstrated therapeutic equivalence of generic perindopril (Parnavel) to the original perindopril.